Purified Recombinant VP2 Protein Can Provide Complete Protection to very Virulent Infectious Bursal Disease Virus Challenge as a Subunit Vaccine - Pang Wenqiang; Zhao Kunkun; Xue Jingjing; Geng Xiaolin; Yuan Yue; Huang Yuxin; Yang Yujie; Jin Yudan; Tian Hui; Wu Peng; Li Xiangdong; Liu Wujie; et al. (Journal of Vaccines and Immunology - Peertechz Publications, 2015)
Background: The very virulent infectious bursal disease virus has become the dominant path type that damage lymphoid tissues with high mortality in young chickens in China. Current commercial vaccines are modified live vaccines originated from classic form of virulent virus and cannot provide complete protection as they cause bursal atrophy and immunosuppression. There is an urgent call to more effective and safer vaccines. Methods: In this study, we successfully expressed the soluble VP2 protein in E.coli and purified recombinant protein by using ion-exchange chromatography. The recombinant protein was subsequently used on chickens as a subunit vaccine. Result: The purified recombinant VP2 protein can generate high agar gel diffusion recipitation antibodies and provide complete protection to a very virulent filed infectious bursal disease virus challenge as shown by results of clinical manifestations and histopathological examination. By contrast,commercial vaccines can only provide 60% protection as compared with recombinant VP2 protein. Conclusion: The subunit vaccine based on recombinant VP2 protein could be a promising vaccine candidate to be used on chickens.